Analysis of the Challenges Faced by Mathematics Education Students in Distance Learning During the Covid-19 Pandemic - Akmal Riswandi; Muhammad Aprizal Irawan; Ismail Suardi Wekke (Scientechno: Journal of Science and Technology, 2024)
Mathematics learning is one of the areas directly affected by the Covid-19 pandemic. The Covid-19 pandemic has resulted in all teaching and learning activities being carried out online, students and lecturers are forced to adapt to the new situation. The aim of this research is to describe the difficulties faced by students majoring in Mathematics Education in online learning, especially in Algebraic Structure courses during the Covid-19 pandemic. This type of research is qualitative research, the subjects of this research are 3rd semester students of Mathematics Education at Alauddin State Islamic University (UIN) Makassar who are taking the Algebraic Structure course. The instruments used in this research were questionnaires, interviews and documentation. The data collection technique was carried out by giving questionnaires in the form of questionnaires and interviews to subjects to examine in more depth the difficulties of mathematics students during online learning during the Covid-19 pandemic. The results of the analysis show that students face several difficulties which are classified into technical difficulties, adaptation difficulties and teacher unpreparedness. To overcome these difficulties, it is necessary to develop learning strategies that are able to support the acceleration of student adaptation in online learning. Apart from that, teachers (lecturers) must also improve their ability to master technology in developing interactive learning media that can be used online and lecturers are also expected to be able to develop varied learning models so that students do not feel bored while studying.